ANALYSIS OF STUDENTS' LEARNING DIFFICULTIES IN PROTIST MATERIAL - Mailin Sonia Gira Sihombing; Hendro Pranoto (Jurnal Pelita Pendidikan, 2021)
This study aims to determine learning difficulties based on students' understanding of protist material for class X IPA in SMA Negeri in Deli Serdang Regency, North Sumatra Province, and the main factors causing students' learning difficulties. The research method used in this research is descriptive quantitative. The sample of this study was taken at random, amounting to five schools. The data collection technique used is a two-tier multiple-choice diagnostic test instrument to identify students' learning difficulties and a questionnaire instrument to determine the causes of students' learning difficulties. The results showed that learning difficulties from the highest to the lowest were analyzing the basic grouping of protists, understanding how protists reproduce, recognizing protist objects, explaining the morphological characteristics of protists, and understanding the role of protists in protists life and grouping protists into several classes. The main factors causing student learning difficulties are the facilities and infrastructure and the nature of the protist material. Good planning of practicum activities, selection of appropriate learning methods, and linking learning to everyday life must be done by teachers to help overcome student learning difficulties.